The Role of Banks of the BRICS Countries in Financing Innovation Projects - Ruslan I. KHASBULATOV; Svetlana A. GUSAROVA; Igor V. GUSAROV; Margarita S. SMERETCHINSKII (Communications of International Proceedings, 2021)
The introduction of innovations into the country's economy is of paramount importance, especially in the face of emerging from the coronavirus pandemic. Significant investments are required to finance innovative projects. Each country is interested not only in the inflow of foreign direct investment, but also in the search for additional sources of financing within the country. Banks' funds can serve as one of such sources. The paper examines the role of the banks of the BRICS countries (Brazil, Russia, India, China, South Africa) in financing innovation projects. Based on the analysis, problems were identified and proposals for the development of this process were developed.
Keywords: BRICS Countries; Banks; Innovation; Financing.